PERLINDUNGAN HUKUM PETANI SEBAGAI KONSUMEN DALAM PERDAGANGAN DAN PEREDARAN PUPUK DITINJAU DARI UNDANG-UNDANG NOMOR 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN (Studi Putusan Nomor 2640K/Pid.Sus/2016) - Chindy Yapin; Ermanto Fahamsyah (Fakultas Hukum Universitas Tarumanagara, 2019)
Fertilizer as a common trading product due to functionality in agricultural sector such as Mushan Munandar’s case where selling and distributing underated fertilizer. The research method that writer using is normative legal research. The purpose of this research is to understand legal protection toward farmers as the user of fertilizer and Judge’s decision on selling and distributing underated fertilizer case refer to Court Decision Number 2640K/Pid.Sus/2016. The result of this research are one, legal protection toward farmers has been implemented practically. By drafting regulation and policy which protect farmers. However, the implementation was ineffective. There were loopholes that have been used by individuals for the sake of their own purposes. Second, Judge’s decision on the case which writer brought up about violation of the consumers did not only refer to current regulation and policy. There were other considerations such as humanity and psychology wellbeing of the suspect become factors that influenced the weight of punishment.